Astana Agreement and the Battle for Eastern Syria - Mr. Sajid Aziz (CISS Insight Journal, 2017)
Syria has seen some important political and military developments in recent months. Russia, Turkey and Iran reached a deal in Astana, capital of Kazakhstan, to establish deescalation areas and hinted for the first time that third party/neutral forces might be deployed to monitor those security zones. Sensing an opportunity in the relative calm brought about by Astana Agreement in northern, central and southern Syria, Assad regime and its allies have started a military offensive in eastern Syria to establish a link between Damascus and remote provinces of Deir ez-Zor and Raqqa and take control of the strategic border crossings. On 8 May, 2017, Trump administration approved extension of military assistance in the shape of mortars, machine guns, ammunition and light-armored vehicles to Syrian Democratic Forces (SDF), a coalition of Kurdish and Arab forces, in their fight against ISIS. America has been fighting ISIS in both Iraq and Syria. After a grueling fight of nine months, American and Iraqi forces have ‘liberated’ Mosul, leaving behind a heap of collapsed building, debris and displaced people. The symbolic and military value of Mosul is immense. It was in Mosul when Abu Bakr Bagdadi declared a caliphate in 2004 in Al-Nuri mosque.